VEGF a zwyrodnienie plamki związane z wiekiem. Część I. Fizjologiczna i patologiczna rola VEGF - Wylęgała, Edward; Teper, Sławomir (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
VEGF, an endothelial specific growth factor, stimulates vascular permeability and angiogenesis. VEGF is involved in many physiological and pathological processes including embryogenesis, wound healing, tumor growth, choroidal neovascularization and many others. Authors discuss VEGF structure, known isoforms and their mechanisms of function, focusing on VEGF influence on eye tissues.